Wiley GAAP 2019 : interpretation and application of generally accepted accounting principles - Flood, Joanne M. (John Wiley & Sons, Inc., 2019)
The most comprehensive guide to FASB Codifications, updated with the latest pronouncements Wiley GAAP 2019 is the essential resource for US GAAP implementation. Covering all codifications by the Financial Accounting Standards Board (FASB)-including the latest updates-this book provides clear explanations and practical examples for real-world application of these dynamic guidelines. Each chapter includes relevant sources of GAAP and expert guidance on interpretation, terminology, relevant concepts, and applicable rules, while in-depth discussion on the issues surrounding specific pronouncements offers informative perspective for a variety of scenarios. This user-friendly reference covers every pronouncement currently in effect or being deliberated-including FASB Technical Bulletins, FASB Implementation Guides, AcSEC Practice Bulletins, and AICPA Accounting Interpretations-in a single volume, fully referenced to the FASB Current Text and cross-referenced to the new FASB codification system. Clear and concise without sacrificing depth or rigor, this invaluable resource simplifies research and helps CPAs and other accounting professionals ensure accuracy and compliance.-Examine the latest changes to US GAAP standards and practices -Gain expert perspectives on the issues surrounding specific pronouncements -Learn how the standards translate to common real-world scenarios -Clarify implementation through numerous illustrations and real-world examples Staying up-to-date with constantly-evolving guidelines is a challenge, but the requirement for accurate interpretation and appropriate application adds an additional layer of complexity in an area where noncompliance could expose an organization to significant risk. Wiley GAAP 2019 provides the guidance, insight, and perspective accounting professionals need to ensure accurate and up-to-date GAAP implementation.